Social consideration in product life cycle for product social sustainability - Rezaei Kalvani, Somayeh; Sharaai, Amir Hamzah; Abdullahi, Ibrahim Kabir (MDPI AG, 2021)
Social life cycle assessment (S-LCA) is an emerging and pivotal tool for sustainability evaluation of products throughout their life cycle. Understanding deeply published papers helps to modify methods and identify research gaps. The aim of this study is to discover the existing gap in the S-LCA of products and to find the weaknesses of the approach. The method of performing the review was a narrative review where published papers from 2006 to 2020 were included through the use of the Web of Science and Scopus databases. S-LCA is considered to be relevant to a majority of sectors and processes (agricultural, industrial, technology, energy, and tourism). However, there is not sufficient research on evaluation of S-LCA on cereal crops and livestock output. It is indicated that, in the present S-LCA studies, there has been a lack of attention paid to the society and value chain actors and final consumer stakeholders. The elements of sexual harassment and employment relationships are not considered in SLCA studies. Italy has the largest amount of cases of S-LCA studies. The major challenges of applying S-LCA (by using site specific data) is data collection, which is time-consuming. It is recommended to evaluate a comprehensive sustainability assessment by adding cost of social assessment to LCA since there has been a lack of attention on assessment of cost in S-LCA.